Comment on Aidan Forth’s, Barbed-Wire Imperialism: Britain’s Empire of Camps, 1876–1903 (Berkeley: University of California Press, 2017) - Gorman, Daniel (Journal of the Canadian Historical Association / Revue de la Société historique du Canada, 2021)
This review essay assesses Aidan Forth’s Barbed-Wire Imperialism: Britain’s Empire of Camps, 1876–1903 within the broader historical context of imperial repression. It looks at how the British used camps as tools of control, how they reflected spatial concepts of imperial rule, and how they challenged the idea of liberal imperialism.